Argentina : Developing Deep and Sustainable Housing Finance Markets - World Bank Group (World Bank, Washington, DC, 2017)
The housing deficit in Argentina is estimated to affect 6 million out of the 24 million households nationally. Macro-economic turmoil has contributed to this imbalance in two ways. First, the continuous inflation and currency depreciation made real estate a refuge investment protecting the capital value of investors. Second, rapid inflation acts a strong deterrent to the provision of long term finance and in particular mortgages. The government overhauled the public housing assistance policy by launching a 2016-2019 integrated housing and habitat plan (plan integral de vivienda y habitat). This plan aims to stimulate the production, or to provide one million housing solutions through two programs: a neighborhood improvement program targeting informal settlements, and a credit-linked subsidy program, solucion casa propria, through which up-front subsidies are granted to first time home buyers who contract mortgages, thus leveraging the impact of public intervention with bank credit. The broad prohibition of indexation has for a long time stunted the provision of long term, finance. To successfully grow the mortgage market, banks need funding and tools to manage interest rate and liquidity risks - that is, in the absence of significant derivative markets, funding from the capital market. The eventual development of a mortgage bond market based on housing loan portfolios, will help to increase the supply of stable long term funding instruments.